Determining anatomical position of the umbilicus in Iranian girls, and providing quantitative indices and formula to determine neo-umbilicus during abdominoplasty - Parnia, Rafi; Ghorbani, Ladan; Sepehrvand, Nariman; Hatami, Sanaz; Bazargan-Hejazi, Shahrzad (Indian Journal of Plastic Surgery, 2012)
Background and Aim: The umbilicus plays an important role in the aesthetic appearance of the abdomen. So, its restoration during reconstructive surgeries, such as an abdominoplasty, is a challenge. The aim of this study was to evaluate quantitative indices based on constant skeletal points in the anterior wall of abdomen in order to provide an appropriate site of a neo-umbilicus during an abdominoplasty. Materials and Methods: In this descriptive, cross-sectional study, we enrolled 65 young adult girls (20-25 years old) who were nulliparous, nulligravid, and without any history of surgery. Weight, height, distance from xiphoid to umbilicus (Xu), distance from the pubic symphysis to xiphosternum (Xp), and anterior superior iliac spine (interASIS) distance of the subjects were measured. Data were analysed by SPSS ver. 16 using descriptive statistics and multiple regression tests in order to present a formula (equation). Results: Mean age was 22.74 ± 1.51 years, mean weight 54.98 ± 6.51 kg, mean height 160.91 ± 4.11 cm and body mass index (BMI) was calculated to be 21.25 ± 2.61 kg/m 2 . Mean Xp distance was 32.26 ± 2.23 cm and mean Xu distance was 17.11 ± 1.64 cm. Xu/Xp ratio (ratio of umbilicoxiphoid distance to puboxiphoid distance) was 53.06 ± 3.9%. Data were analysed using multiple regression test and likelihood ratio. The formula used in determining the appropriate site of neo-umbilicus during abdominoplasty was suggested: Xu=−0.98 + 0.91Xp − 0.07H. Conclusion: By applying these quantitative methods, the natural site of neo-umbilicus could be determined. This may reduce practice errors and increase patient satisfaction. In addition, these findings provide plausible evidence to defend against possible legal complaints.
Keywords: Abdominoplasty; neo-omphaloplasty; umbilicus